Reconstruction of daily photosynthetically active radiation and its trends over China. Issue 23 (12th December 2013) - Tang, Wenjun; Qin, Jun; Yang, Kun; Niu, Xiaolei; Zhang, Xiaotong; Yu, Yu; Zhu, Xudong
Abstract [1] Photosynthetically active radiation (PAR) is widely required in ecological studies, but it is not routinely measured at China Meteorological Administration (CMA) stations. In this study, a PAR model is utilized to estimate daily PAR from routine meteorological parameters (air temperature, air pressure, relative humidity, and sunshine duration) at CMA stations. The estimate is evaluated against measurements at 10 Chinese Ecosystem Research Network (CERN) stations. The model can produce PAR with mean bias errors of −2.4 W m−2, root mean square errors of 14.0 W m−2, and correlation coefficient (R) of 0.92 at all CERN stations. Comparison with a locally calibrated model indicates that the estimate has a comparable or even higher accuracy than the local model calibrated with CERN data. Another evaluation at an independent site further indicates that our estimate has higher accuracy than the local model at stations independent of CERN. Finally, a 50 year data set of daily PAR at 716 CMA stations over China is reconstructed by the validated model, and its climatology and long‐term variations over China are analyzed. The data set would substantially contribute to ecological studies in China.